Cover Image. (2nd November 2017) - Le Pogam, Pierre; Boustie, Joël; Richomme, Pascal; Denis, Antoine; Schinkovitz, Andreas
Abstract : The cover image, by Pierre Le Pogam et al., is based on the Research Article The inherent matrix properties of lichen metabolites in MALDI‐TOF MS, DOI:10.1002/rcm.7980 . Photo Credit: Joёl Boustie.